Anglo-Saxon(ist) pasts, postSaxon futures - Ellard, Donna Beth (Punctum Books, 2019)
"Over the past several years, Anglo-Saxon studies-alongside the larger field of medieval studies-has undergone a reckoning. Outcries against the misogyny and sexism of prominent figures in the field have quickly turned to issues of racism, prompting Anglo-Saxonists to recognize an institutional, structural whiteness that not only bars the door to people of color but also prohibits scholars from confronting the very idea that race and racism operate within the field's scholarship, scholarly practices, and intellectual history. Anglo-Saxon(ist) Pasts, postSaxon Futures traces the integral role that colonialism and racism play in Anglo-Saxon studies by tracking the development of the "Anglo-Saxonist," an overtly racialized term that describes a person whose affinities point towards white nationalism. That scholars continue to call themselves "Anglo-Saxonists," despite urgent calls to combat racism within the field, suggests that this term is much more than just a professional appellative. It is, this book argues, a ghost in the machine of Anglo-Saxon studies-a spectral figure created by a group of nineteenth-century historians, archaeologists, and philologists responsible for not only framing the interdisciplinary field of Anglo-Saxon studies but for also encoding ideologies of British colonialism and Anglo-American racism within the field's methods and pedagogies. Anglo-Saxon(ist) pasts, postSaxon Futures is at once a historiography of Anglo-Saxon studies, a mourning of its Anglo-Saxonist "fathers," and an exorcism of the colonial-racial ghosts that lurk within the field's scholarly methods and pedagogies. Part intellectual history, part grief work, this book leverages the genres of literary criticism, auto-ethnography, and creative nonfiction in order to confront Anglo-Saxonist pasts in order to imagine speculative postSaxon futures inclusive of voices and bodies heretofore excluded from the field of Anglo-Saxon studies"--